A History of Islamic Philosophy, 3d ed. - Anita Mir (International Institute of Islamic Thought, 2006)
That Majid Fakhry’s A History of Islamic Philosophy, first published in 1970, has been brought out in a third revised edition can be of no surprise to the many admirers of this most robust of scholars. Fakhry’s scholarship is meticulous, and his style, even when handling the most complex ideas, remains simple and straightforward. As many of the theological questions raised by Islam’s key philosophers, particularly those pertaining to free will, justice, rights, and responsibilities, had political implications, each chapter in this book begins with a historical context. However, Fakhry only allows this context to play a subsidiary role, as a backdrop to the main narrative: the history of ideas. This approach lends itself very well to an examination of the ideas held by both individual philosophers and schools of philosophy. Importantly, Fakhry demonstrates how, during several key Islamic epochs, there was no one dominant system of thought, but rather, contending systems of thought. He takes us through these debates step by step, as in, for example, the first theological controversy on free will and predestination (qadar). It is in the presentation of these debates, more than anywhere else, that we see that while A History of Islamic Philosophy is distinguished from the work of many other grand narrative histories by not being marred by a partisan viewpoint, Fakhry’s is by no means a clinically scientific approach. This book comprises thirteen chapters. It begins with “The Legacy of Greece, Alexandria, and the Orient,” covers the watershed periods in the ...